Surgical Treatment of Impression-compression Fractures of Tibial Condyles - Vakhitov, B. I. (Asian Journal of Pharmaceutics (AJP), 2019)
Objective: The Department of Traumatology of the SRCT â€œWTOâ€ - the Center of Traumatology of the Republican Clinical Hospital - has been developed and successfully applies various clinically substantiated assemblies of the spoke and rod external fixation devices on the basis of G.A. Ilizarov method. The assemblies are easy to use, convenient, and comfortable for patients. Experimental: We have presented and justified the problem of surgical treatment of tibial condyle impression-compression fractures. They showed the features of transosseous osteosynthesis by external fixation devices at various kinds of fractures, depending on the destruction of tibia plateau articulate surface. Results and Discussion: They performed the analysis of operative treatment among 65 patients with impression-compression fractures of the proximal articular part of the tibia. During the treatment, they applied clinical, X-ray (including X-ray tomography data), and biomechanical (the research on the NeuroCom Balance Master diagnostic and treatment complex) research methods. The analysis of treatment outcomes among 65 patients with the consequences of impression compression fractures of the tibial condyles showed good reposition capabilities of the methods developed and applied by us and the arrangements of the spoke-rod devices of external fixation. Conclusions: Excellent and good results of treatment were achieved in 72.3% of cases of severe intraarticular lesions. Transosseous osteosynthesis by external fixation devices can be used for various types of knee joint fractures.